The Role of Perceived Value as a Mediating Variable in Purchasing Decisions on Shopee E-Commerce: A Study of Gen Z - Nugroho, Irfan Adi; Hartanto, Prasetyo (SAFE-Network, 2026)
This study aims to analyze the role of perceived value as a mediating variable in the relationship between brand trust and online customer reviews on purchasing decisions in Shopee e-commerce among Generation Z. This study uses a positivist and deductive approach, with a quantitative method through a survey of Generation Z respondents who actively shop on Shopee. The data obtained were analyzed using the Structural Equation Modeling (SEM) method to test the relationship between the research variables, with individual analysis units, minimal research involvement, and a noncontrived research setting. The results showed that Brand Trust and Online Customer Reviews had a positive effect on Perceived Value and Purchasing Decisions, and Perceived Value was proven to mediate the relationship between the independent variables and purchasing decisions. These findings have implications for e-commerce players in improving consumer trust and shopping experience to encourage purchasing decisions.